pH-responsive carboxylic cellulose acetate nanoparticles for controlled release of penicillin G - Ho, Boon-Kui; Chin, Suk Fun; Pang, Suh Cem (Elsevier B.V, 2020)
In this study, pH responsive carboxylic cellulose acetate nanoparticles (CCA NPs) have been evaluated as drug nanocarriers for controlled release of drug. Herein, carboxylic cellulose acetate (CCA) was initially synthesized via oxidation of cellulose using a 2,2,6,6- tetramethylpiperidin-1-yl)oxidanyl (TEMPO) as an oxidant and followed by the acetylation of carboxylic cellulose in the presence of iodine as a catalyst. CCA NPs were then obtained via the nanoprecipitation process and subsequent sonication. The obtained CCA NPs with a mean diameter of 96 nm were subsequently evaluated as drug delivery nanocarriers. Penicillin G as a model drug was loaded onto the CCA NPs via the adsorption process. Drug release profiles of Penicillin G from CCA NPs were evaluated in phosphate buffer solution (PBS) at different medium pH values (1.2, 7.4, and 8.6). Release kinetic models were applied to determine the release mechanism of penicillin G from loaded CCA NPs. Results showed that pH-responsive release of penicillin G from CCA NPs which was released most slowly at medium of pH 7.4.